Perspectives on the Human Body in the 20th-Century Book of Remedies, Rafaʾel ha-Malʾakh. (2nd January 2019) - Tuszewicki, Marek
ABSTRACT: The book of remedies Rafaʾel ha-Malʾakh appeared in Hebrew at the beginning of the twentieth century. Its author, rabbi Yehuda Yudl Rosenberg, a man shaped by traditional Judaism and Hasidism, set himself the goal of creating a practical medical guide addressed to the poorer sections of the Jewish population in Russian Poland. In his work he included a diverse body of material representing a number of often conflicting views on the human body. The aim of this article is to explore the main elements shaping the ideas contained in the guide, with particular emphasis on Rosenberg's traditionalist views, which is echoed in early-modern medical publications and in ethnographic collections from the turn of the nineteenth and twentieth centuries. Alongside the pathology of the four humors, the most influential medical theory until the rise of modern medicine, Rosenberg's belief in the relationship between health and the spiritual life of man will be examined through an analysis of the advice provided in Rafaʾel ha-Malʾakh. Moreover, the article draws attention to Rosenberg's dialogue with modernity and seeks to answer the question whether this handbook advocated a modern approach towards the treatment of illness.